Assessment of the Effect of FDI on Employment in the Enterprise Sector in Vietnam - Thuy, Dao Thi Bich (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 5E, 2020)
Since the Foreign Investment Law was first promulgated in Vietnam in 1987, the inflows of FDI to the country have increased significantly over the years. Among the contributions of FDI to the socio-economic development of the country, interest is placed on employment creation. The purpose of this study is to assess the effect of FDI on employment in the enterprise sector in Vietnam. The empirical study is conducted at the local level with all 63 provinces nationwide in the period from 2006 to 2014. The results reveal that FDI enterprises have a higher effect on employment creation than domestic enterprises. Beside, a positive relation between the share of FDI enterprises (in terms of the size of FDI in relative to the total capital resource) and the growth of employment in the enterprise sector is found which implies that the relatively larger presence of FDI enterprises can have positive spillover effects on employment growth. However, the spillover effects of FDI are considered limited.